Risk factors of cardiovascular disease in patients with diabetes mellitus type 2Przew Lek 2005; 3: 46-52 - Krasnodębski, Przemysław (Przewodnik Lekarza/Guide for GPs, 2005)
Cardiovascular disease is the main cause of increased mortality in diabetes patients. Myocardial infraction and stroke is in 60 to 80% causes reason of death in patients with type 2 diabetes mellitus. The main risk factors of cardiovascular disease are: hyperglycaemia, hyperinsulinaemia, insulin resistance, dyslipidaemia and hypertension. The other atherosclerosis risk factors are: smoking; increased levels of homocystein, C-reactive protein and fibrinogen. The key pathogenetic mechanism of diabetic vascular complications is increased oxidative stress due to chronic hiperglycaemia. Oxygen-derived free radicals cause lipoprotein oxidation, endothelial dysfunction, platelets hiperreactivity and blood clotting disorders. Determination of the role of this risk factors in patogenesis of diabetic angiopathy may be of significant importance in their effective therapy.